Carbon capture in breweries using microalgae: Preliminary techno-economic insights for ruminant feed applications - Kira J. Picknell; Nature Poddar; Mathieu Pernice; Janice McCauley; Oscar McMahon; Richard Adamson; Peter J. Ralph (Bioresource Technology, 2026)

Explainable artificial intelligence for predicting rare earth elements leaching from secondary resources - Quang Loc Nguyen; Huy Nguyen Lai; Hong T.M. Nguyen; Le Long Pham; Andrei Herdean; Nature Poddar; Unnikrishnan Kuzhiumparambil; Ai Nguyen; Mathieu Pernice; Peter J. Ralph; Phong H.N. Vo (Journal of Hazardous Materials, 2025)

Harnessing microalgae for finfish nutrition: advances in biotechnology and aquafeed development - Justin Tierney; Peter J. Ralph; Igor Pirozzi; Mathieu Pernice (Frontiers in Marine Science, 2025)
Finfish aquaculture is a key contributor to global seafood production, providing quality protein to consumers across the world, however, the search for regenerative, cost-effective and scalable raw materials continues. Alternatives to wild-caught fish have been explored extensively with limited success. Among the most promising alternatives is autotrophic marine microalgae as they produce essential fatty acids, amino acids and bioactive compounds that support fish growth and immune function. However, their development into aquafeed is limited due to cost. By considering the major benefits of microalgae in aquafeed, as well as biotechnological advancements in the industry, this review aims to consolidate multi-disciplinary findings and highlight research opportunities to facilitate widespread adoption of microalgae into aquafeed.

Rheological characterization and modeling of freshwater and marine microalgae and cyanobacteria mixed cultures - Conor Button; Nature Poddar; Tom Lacassagne; Mathieu Pernice; Vishal Gupta; Lisa Aditya; Unnikrishnan Kuzhiumparambil; Peter J. Ralph (Algal Research, 2025)

Random mutagenesis using cold atmospheric plasma to produce mutant microalgae for hyper-recovery of rare earth elements from mining materials - Phong H.N. Vo; Mikael Kim; Unnikrishnan Kuzhiumparambil; Cora Hinkley; Jungmi Hong; Tianqi Zhang; Mathieu Pernice; Patrick J. Cullen; Peter J. Ralph (Chemical Engineering Journal, 2025)

Microalgae-bacteria consortia for organic pollutants remediation from wastewater: A critical review - Tan Phat Vo; Soroosh Danaee; Chawalit Chaiwong; Bao Tran Pham; Nature Poddar; Mikael Kim; Unnikrishnan Kuzhiumparambil; Chris Songsomboon; Mathieu Pernice; Huu Hao Ngo; Peter J. Ralph; Phong H.N. Vo (Journal of Environmental Chemical Engineering, 2024)

Biomining using microalgae to recover rare earth elements (REEs) from bauxite - Phong H.N. Vo; Unnikrishnan Kuzhiumparambil; Mikael Kim; Cora Hinkley; Mathieu Pernice; Long D. Nghiem; Peter J. Ralph (Bioresource Technology, 2024)

Differential gene expression in a subpopulation of Phaeodactylum tricornutum with enhanced growth and carotenoid production after FACS-mediated selection - Sean Macdonald Miller; Andrei Herdean; Vishal Gupta; Brandon Signal; Raffaela M. Abbriano; Peter J. Ralph; Mathieu Pernice (Journal of Applied Phycology, 2023)
Fluorescence-Activated Cell Sorting (FACS) is a powerful method with many applications in microalgal research, especially for screening and selection of cells with improved phenotypes. However, the technology requires review of gene expression changes responsible for enhanced phenotypes in sorted populations. Phaeodactylum tricornutum cells were sorted using FACS with excitation/emission parameters targeted to favouring the industrially-relevant carotenoid fucoxanthin. The resulting cultures showed significantly higher growth rate (1.10 ×), biomass (1.30 ×), chlorophyll a levels (1.22 ×) and fucoxanthin content (1.28 ×) relative to the wild-type strain. RNA-seq was used to elucidate the underlying molecular-level regulatory changes associated with these traits and represents the first study do so on FACS-sorted microalgal cultures. Transcriptome analysis corroborated evidence of increased chlorophyll a and fucoxanthin, showing enrichment for the genes/pathways for tetrapyrrole biosynthesis and for suites of genes directly related to photosynthesis. Only three genes were upregulated in the MEP (non-mevalonate) pathway to carotenoid biosynthesis pathway, suggesting either a strong influence of IDI , CRTISO5 and ZEP1 on fucoxanthin biosynthesis or a post-transcriptional or post-translational mechanism for the observed increase in fucoxanthin content.

Exploring the potential of algae-bacteria interactions in the biocontrol of the marine pathogen Vibrio parahaemolyticus - Breanna Osborne; Nachshon Siboni; Justin R. Seymour; Peter Ralph; Mathieu Pernice (Journal of Applied Phycology, 2023)
The marine bacterium Vibrio parahaemolyticus is the leading cause of seafood-related food poisoning worldwide and a pathogen of marine species harvested in aquaculture. An outbreak of pathogenic V. parahaemolyticus within crustacean and bi-valve aquaculture facilities often results in significant loss of farmed product and in the spread of the pathogen into the human population. Evidence shows several marine bacteria and microalgae species have antibacterial effects against marine pathogens, including V. parahaemolyticus . This study explored the potential of combining possible mutualistic species as a consortium to enhance antibacterial properties against V. parahaemolyticus . Marine bacteria and microalgae were screened with the aim of identifying those able to successfully coexist while demonstrating growth suppression of multiple V. parahaemolyticus strains. This trial involved four screening phases to find effective inhibitor species and to gain insight into species-specific influences on cell growth. The combination of Tetraselmis sp. and Pseudoalteromonas peptidolytica achieved the greatest inhibition rate of V. parahaemolyticus of all combinations. This pairing resulted in the significant reduction of up to 24 ± 15% in Vibrio sp. copy number mL −1 day −1 in two of the five examined V. parahaemolyticus strains within five days, compared to control cultures absent of probiotic bacteria. Applying probiotic consortia such as this has the potential for use as a biocontrol technique within mariculture, but it will require additional research into the self-sustainability of successful consortia in natural aquatic conditions.

Heat-evolved microalgal symbionts increase thermal bleaching tolerance of coral juveniles without a trade-off against growth - Kate M. Quigley; Carlos Alvarez-Roa; Jean-Baptiste Raina; Mathieu Pernice; Madeleine J. H. van Oppen (Coral Reefs, 2023)
Global climate change is threatening the persistence of coral reefs as associated summer heatwaves trigger the loss of microalgal endosymbionts (Symbiodiniaceae) from the coral tissues, or coral bleaching. We infected aposymbiotic juveniles of the coral Acropora tenuis with either wildtype (WT10) or heat-evolved (SS1 or SS8) Symbiodiniaceae strains Cladocopium proliferum (formerly referred to as Cladocopium goreaui and Cladocopium C1 acro ). After 10 months at 27 °C, SS8-juveniles were 2 × larger than SS1- or WT10-juveniles. In response to a simulated heatwave (31 °C for 41 days), the WT10-juveniles bleached and showed a decline in respiration while cell densities and respiration in both SS-juvenile groups remained unchanged compared to the controls. These results reveal that some heat-evolved strains can increase the bleaching tolerance of juvenile corals without a trade-off against growth. This response is opposite to the lower nutrient provisioning often reported for naturally thermotolerant Symbiodiniaceae (e.g. genus Durusdinium ) , thereby offering enhanced fitness to the host without the ecological consequences of diminished growth.

Signs of local adaptation by genetic selection and isolation promoted by extreme temperature and salinity in the Mediterranean seagrass Posidonia oceanica - Hung Manh Nguyen; Miriam Ruocco; Emanuela Dattolo; Federica Paola Cassetti; Sebastiano Calvo; Agostino Tomasello; Lázaro Marín‐Guirao; Mathieu Pernice; Gabriele Procaccini (Molecular Ecology, 2023)
Adaptation to local conditions is known to occur in seagrasses; however, knowledge of the genetic basis underlying this phenomenon remains scarce. Here, we analysed Posidonia oceanica from six sites within and around the Stagnone di Marsala, a semi‐enclosed coastal lagoon where salinity and temperature exceed the generally described tolerance thresholds of the species. Sea surface temperatures (SSTs) were measured and plant samples were collected for the assessment of morphology, flowering rate and for screening genome‐wide polymorphisms using double digest restriction‐site‐associated DNA sequencing. Results demonstrated more extreme SSTs and salinity levels inside the lagoon than the outer lagoon regions. Morphological results showed significantly fewer and shorter leaves and reduced rhizome growth of P. oceanica from the inner lagoon and past flowering events were recorded only for a meadow farthest away from the lagoon. Using an array of 51,329 single nucleotide polymorphisms, we revealed a clear genetic structure among the study sites and confirmed the genetic isolation and high clonality of the innermost site. In all, 14 outlier loci were identified and annotated with several proteins including those relate to plant stress response, protein transport and regulators of plant‐specific developmental events. Especially, five outlier loci showed maximum allele frequency at the innermost site, likely reflecting adaptation to the extreme temperature and salinity regimes, possibly due to the selection of more resistant genotypes and the progressive restriction of gene flow. Overall, this study helps us to disentangle the genetic basis of seagrass adaptation to local environmental conditions and may support future works on assisted evolution in seagrasses.

Disparate Inventories of Hypoxia Gene Sets Across Corals Align With Inferred Environmental Resilience - Rachel Alderdice; Benjamin C. C. Hume; Michael Kühl; Mathieu Pernice; David J. Suggett; Christian R. Voolstra (Frontiers in Marine Science, 2022)
Aquatic deoxygenation has been flagged as an overlooked but key factor contributing to mass bleaching-induced coral mortality. During deoxygenation events triggered by coastal nutrient pollution and ocean warming, oxygen supplies lower to concentrations that can elicit an aerobic metabolic crisis i.e., hypoxia. Surprisingly little is known of the fundamental hypoxia gene set inventory that corals possess to respond to lowered oxygen (i.e., deoxygenation). For instance, it is unclear whether gene copy number differences exist across species that may affect the efficacy of a measured transcriptomic stress response. Therefore, we conducted an ortholog-based meta-analysis to investigate how hypoxia gene inventories differ amongst coral species to assess putative copy number variations (CNVs). We specifically elucidated CNVs for a compiled list of 32 hypoxia genes across 24 protein sets from species with a sequenced genome spanning corals from the robust and complex clade. We found approximately a third of the investigated genes exhibited copy number differences, and these differences were species-specific rather than attributable to the robust-complex split. Interestingly, we consistently found the highest gene expansion present in Porites lutea , which is considered to exhibit inherently greater stress tolerance than other species. Consequently, our analysis suggests that hypoxia stress gene expansion may coincide with increased stress tolerance. As such, the unevenly expanded (or reduced) hypoxia genes presented here provide key genes of interest to target in examining (or diagnosing) coral stress responses. Important next steps will involve determining to what extent such gene copy differences align with certain coral traits.

Hypoxia as a physiological cue and pathological stress for coral larvae - Rachel Alderdice; Mathieu Pernice; Anny Cárdenas; David J. Hughes; Peter L. Harrison; Nadine Boulotte; Katie Chartrand; Michael Kühl; David J. Suggett; Christian R. Voolstra (Molecular Ecology, 2022)
Ocean deoxygenation events are intensifying worldwide and can rapidly drive adult corals into a state of metabolic crisis and bleaching‐induced mortality, but whether coral larvae are subject to similar stress remains untested. We experimentally exposed apo‐symbiotic coral larvae of Acropora selago to deoxygenation stress with subsequent reoxygenation aligned to their night‐day light cycle, and followed their gene expression using RNA‐Seq. After 12 h of deoxygenation stress (~2 mg O 2 /L), coral planulae demonstrated a low expression of HIF‐targeted hypoxia response genes concomitant with a significantly high expression of PHD2 (a promoter of HIFα proteasomal degradation), similar to corresponding adult corals. Despite exhibiting a consistent swimming phenotype compared to control samples, the differential gene expression observed in planulae exposed to deoxygenation‐reoxygenation suggests a disruption of pathways involved in developmental regulation, mitochondrial activity, lipid metabolism, and O 2 ‐sensitive epigenetic regulators. Importantly, we found that treated larvae exhibited a disruption in the expression of conserved HIF‐targeted developmental regulators, for example, Homeobox ( HOX ) genes, corroborating how changes in external oxygen levels can affect animal development. We discuss how the observed deoxygenation responses may be indicative of a possible acclimation response or alternatively may imply negative latent impacts for coral larval fitness.

Photo-physiology and morphology reveal divergent warming responses in northern and southern hemisphere seagrasses - Hung Manh Nguyen; Fabio Bulleri; Lázaro Marín-Guirao; Mathieu Pernice; Gabriele Procaccini (Marine Biology, 2021)

Symbiont shuffling across environmental gradients aligns with changes in carbon uptake and translocation in the reef-building coral Pocillopora acuta - Mickael Ros; David J. Suggett; John Edmondson; Trent Haydon; David J. Hughes; Mikael Kim; Paul Guagliardo; Jeremy Bougoure; Mathieu Pernice; Jean-Baptiste Raina; Emma F. Camp (Coral Reefs, 2021)

Divergent expression of hypoxia response systems under deoxygenation in reef‐forming corals aligns with bleaching susceptibility - Rachel Alderdice; David J. Suggett; Anny Cárdenas; David J. Hughes; Michael Kühl; Mathieu Pernice; Christian R. Voolstra (Global Change Biology, 2021)
Exposure of marine life to low oxygen is accelerating worldwide via climate change and localized pollution. Mass coral bleaching and mortality have recently occurred where reefs have experienced chronic low oxygen events. However, the mechanistic basis of tolerance to oxygen levels inadequate to sustain normal functioning (i.e. hypoxia) and whether it contributes to bleaching susceptibility, remain unknown. We therefore experimentally exposed colonies of the environmentally resilient Acropora tenuis , a common reef‐building coral from the Great Barrier Reef, to deoxygenation–reoxygenation stress that was aligned to their natural night–day light cycle. Specifically, the treatment involved removing the ‘night‐time O 2 buffer’ to challenge the inherent hypoxia thresholds. RNA‐Seq analysis revealed that coral possess a complete and active hypoxia‐inducible factor (HIF)‐mediated hypoxia response system (HRS) homologous to other metazoans. As expected, A. tenuis exhibited bleaching resistance and showed a strong inducibility of HIF target genes in response to deoxygenation stress. We applied this same approach in parallel to a colony of Acropora selago , known to be environmnetally susceptible, which conversely exhibited a bleaching phenotype response. This phenotypic divergence of A. selago was accompanied by contrasting gene expression profiles indicative of varied effectiveness of their HIF‐HRS. Based on our RNA‐Seq analysis, we propose (a) that the HIF‐HRS is central for corals to manage deoxygenation stress and (b) that key genes of this system (and the wider gene network) may contribute to variation in coral bleaching susceptibility. Our analysis suggests that heat shock protein (hsp) 70 and 90 are important for low oxygen stress tolerance and further highlights how hsp90 expression might also affect the inducibility of coral HIF‐HRS in overcoming a metabolic crisis under deoxygenation stress. We propose that differences in coral HIF‐HRS could be central in regulating sensitivity to other climate change stressors—notably thermal stress—that commonly drive bleaching.

Seagrass rhizosphere microenvironment alters plant‐associated microbial community composition - Kasper Elgetti Brodersen; Nachshon Siboni; Daniel A. Nielsen; Mathieu Pernice; Peter J. Ralph; Justin Seymour; Michael Kühl (Environmental Microbiology, 2018)
Summary The seagrass rhizosphere harbors dynamic microenvironments, where plant‐driven gradients of O 2 and dissolved organic carbon form microhabitats that select for distinct microbial communities. To examine how seagrass‐mediated alterations of rhizosphere geochemistry affect microbial communities at the microscale level, we applied 16S rRNA amplicon sequencing of artificial sediments surrounding the meristematic tissues of the seagrass Zostera muelleri together with microsensor measurements of the chemical conditions at the basal leaf meristem (BLM). Radial O 2 loss (ROL) from the BLM led to ∼ 300 µm thick oxic microzones, wherein pronounced decreases in H 2 S and pH occurred. Significantly higher relative abundances of sulphate‐reducing bacteria were observed around the meristematic tissues compared to the bulk sediment, especially around the root apical meristems (RAM; ∼ 57% of sequences). Within oxic microniches, elevated abundances of sulphide‐oxidizing bacteria were observed compared to the bulk sediment and around the RAM. However, sulphide oxidisers within the oxic microzone did not enhance sediment detoxification, as rates of H 2 S re‐oxidation here were similar to those observed in a pre‐sterilized root/rhizome environment. Our results provide novel insights into how chemical and microbiological processes in the seagrass rhizosphere modulate plant‐microbe interactions potentially affecting seagrass health.

Low oxygen affects photophysiology and the level of expression of two-carbon metabolism genes in the seagrass Zostera muelleri - Mikael Kim; Kasper Elgetti Brodersen; Milán Szabó; Anthony W. D. Larkum; John A. Raven; Peter J. Ralph; Mathieu Pernice (Photosynthesis Research, 2018)

A molecular physiology basis for functional diversity of hydrogen peroxide production amongst Symbiodinium spp. (Dinophyceae) - Samantha Goyen; Mathieu Pernice; Milán Szabó; Mark E. Warner; Peter J. Ralph; David J. Suggett (Marine Biology, 2017)

The emergence of molecular profiling and omics techniques in seagrass biology; furthering our understanding of seagrasses - Peter A. Davey; Mathieu Pernice; Gaurav Sablok; Anthony Larkum; Huey Tyng Lee; Agnieszka Golicz; David Edwards; Rudy Dolferus; Peter Ralph (Functional & Integrative Genomics, 2016)

Microenvironment and phylogenetic diversity of P rochloron inhabiting the surface of crustose didemnid ascidians - Daniel A. Nielsen; Mathieu Pernice; Martin Schliep; Gaurav Sablok; Thomas C. Jeffries; Michael Kühl; Daniel Wangpraseurt; Peter J. Ralph; Anthony W. D. Larkum (Environmental Microbiology, 2015)
Summary The cyanobacterium P rochloron didemni is primarily found in symbiotic relationships with various marine hosts such as ascidians and sponges. P rochloron remains to be successfully cultivated outside of its host, which reflects a lack of knowledge of its unique ecophysiological requirements. We investigated the microenvironment and diversity of P rochloron inhabiting the upper, exposed surface of didemnid ascidians, providing the first insights into this microhabitat. The pH and O 2 concentration in this P rochloron biofilm changes dynamically with irradiance, where photosynthetic activity measurements showed low light adaptation (E k ∼80 ± 7 μmol photons m −2 s −1 ) but high light tolerance. Surface P rochloron cells exhibited a different fine structure to P rochloron cells from cloacal cavities in other ascidians, the principle difference being a central area of many vacuoles dissected by single thylakoids in the surface P rochloron . Cyanobacterial 16S rDNA pyro‐sequencing of the biofilm community on four ascidians resulted in 433 operational taxonomic units ( OTUs ) where on average −85% (65–99%) of all sequence reads, represented by 136 OTUs , were identified as P rochloron via blast search. All of the major P rochloron ‐ OTUs clustered into independent, highly supported phylotypes separate from sequences reported for internal P rochloron , suggesting a hitherto unexplored genetic variability among P rochloron colonizing the outer surface of didemnids.

A nanoscale secondary ion mass spectrometry study of dinoflagellate functional diversity in reef‐building corals - Mathieu Pernice; Simon R. Dunn; Linda Tonk; Sophie Dove; Isabelle Domart‐Coulon; Peter Hoppe; Arno Schintlmeister; Michael Wagner; Anders Meibom (Environmental Microbiology, 2015)
Summary Nutritional interactions between corals and symbiotic dinoflagellate algae lie at the heart of the structural foundation of coral reefs. Whilst the genetic diversity of S ymbiodinium has attracted particular interest because of its contribution to the sensitivity of corals to environmental changes and bleaching (i.e. disruption of coral–dinoflagellate symbiosis), very little is known about the in hospite metabolic capabilities of different S ymbiodinium types. Using a combination of stable isotopic labelling and nanoscale secondary ion mass spectrometry ( NanoSIMS ), we investigated the ability of the intact symbiosis between the reef‐building coral I sopora palifera , and S ymbiodinium C or D types, to assimilate dissolved inorganic carbon (via photosynthesis) and nitrogen (as ammonium). Our results indicate that S ymbiodinium types from two clades naturally associated with I . palifera possess different metabolic capabilities. The S ymbiodinium C type fixed and passed significantly more carbon and nitrogen to its coral host than the D type. This study provides further insights into the metabolic plasticity among different S ymbiodinium types in hospite and strengthens the evidence that the more temperature‐tolerant S ymbiodinium D type may be less metabolically beneficial for its coral host under non‐stressful conditions.

The in situ light microenvironment of corals - Daniel Wangpraseurt; Lubos Polerecky; Anthony W.D. Larkum; Peter J. Ralph; Daniel A. Nielsen; Mathieu Pernice; Michael Kühl (Limnology and Oceanography, 2014)
We used a novel diver‐operated microsensor system to collect in situ spectrally resolved light fields on corals with a micrometer spatial resolution. The light microenvironment differed between polyp and coenosarc tissues with scalar irradiance (400–700 nm) over polyp tissue, attenuating between 5.1‐ and 7.8‐fold from top to base of small hemispherical coral colonies, whereas attenuation was at most 1.5‐fold for coenosarc tissue. Fluctuations in ambient solar irradiance induced changes in light and oxygen microenvironments, which were more pronounced and faster in coenosarc compared with polyp tissue. Backscattered light from the surrounding benthos contributed > 20% of total scalar irradiance at the coral tissue surface and enhanced symbiont photosynthesis and the local O 2 concentration, indicating an important role of benthos optics for coral ecophysiology. Light fields on corals are species and tissue specific and exhibit pronounced variation on scales from micrometers to decimeters. Consequently, the distribution, genetic diversity, and physiology of coral symbionts must be coupled with the measurements of their actual light microenvironment to achieve a more comprehensive understanding of coral ecophysiology.

Validation of Housekeeping Genes for Gene Expression Studies in Symbiodinium Exposed to Thermal and Light Stress - Nedeljka N. Rosic; Mathieu Pernice; Mauricio Rodriguez-Lanetty; Ove Hoegh-Guldberg (Marine Biotechnology, 2011)

Novel natural parabens produced by a Microbulbifer bacterium in its calcareous sponge host Leuconia nivea - Elodie Quévrain; Isabelle Domart‐Coulon; Mathieu Pernice; Marie‐Lise Bourguet‐Kondracki (Environmental Microbiology, 2009)
Summary A broad variety of natural parabens, including four novel structures and known ethyl and butyl parabens, were obtained from culture of a Microbulbifer sp. bacterial strain isolated from the temperate calcareous marine sponge Leuconia nivea (Grant 1826). Their structures were elucidated from spectral analysis, including mass spectrometry and 1D and 2D nuclear magnetic resonance. Their antimicrobial activity evaluated against Staphylococcus aureus was characterized by much higher in vitro activity of these natural paraben compounds 3–9 than commercial synthetic methyl and propyl parabens, usually used as antimicrobial preservatives. Compounds 4 and 9 revealed a bacteriostatic effect and compounds 6 and 7 appeared as bactericidal compounds. Major paraben compound 6 was also active against Gram positive Bacillus sp. and Planococcus sp. sponge isolates and was detected in whole sponge extracts during all seasons, showing its persistent in situ production within the sponge. Moreover, Microbulbifer sp. bacteria were visualized in the sponge body wall using fluorescence in situ hybridization with a probe specific to L4‐n2 phylotypes. Co‐detection in the sponge host of both paraben metabolites and Microbulbifer sp. L4‐n2 indicates, for the first time, production of natural parabens in a sponge host, which may have an ecological role as chemical mediators.

Primary co-culture as a complementary approach to explore the diversity of bacterial associations in marine invertebrates: the example of Nautilus macromphalus (Cephalopoda: Nautiloidea) - Mathieu Pernice; Delphine Pichon; Isabelle Domart-Coulon; Jocelyne Favet; Renata Boucher-Rodoni (Marine Biology, 2007)